High altitude might increase risk of incident frailty in older adults: a nationwide longitudinal survey - Yongfei Dong; Qianqian Wang; Xichao Wang; Can Liu; Ibrar Hussain; Hongmei Ma; Ke Lu; Zaixiang Tang (BMC Public Health)
Abstract Background The number of residents at high altitude is high globally, yet few studies have been conducted on the association between altitude and incident frailty. We evaluated the prospective association and dose-response relationship between altitude and frailty among Chinese older adults. Methods We conducted a prospective cohort study using data from the China Health and Retirement Longitudinal Survey (CHARLS) from 2013 to 2018, enrolling 4065 participants aged ≥ 60 years at baseline. Frailty was assessed using a frailty index (FI) containing 29 health deficit indicators constructed. Cox proportional hazard regression and linear mixed model were used to analyze the association of altitude with frailty. Restricted Cubic Spline regression was used to assess the dose-response relationship between them. Results After a median follow-up of 61 months, 1076 (26.5%) frailty events were documented, including 137 (32.2%) in the middle and 939 (25.8%) in the low altitude group. The FI in the middle altitude group was higher than that in the low altitude group at three waves (baseline = 2013, wave 1 = 2015, and wave 2 = 2018 years). The risk of incident frailty was increased by 24% (HR = 1.24, 95%CI: 1.03–1.48) in the middle altitude group compared to the low altitude group. The FI increased with increasing altitude. The RCS revealed an increased risk of developing frailty at altitudes above 2,000 m. Conclusions Exposure to high altitude is associated with an elevated risk of incident frailty. which suggested that early intervention with high-altitude residents can delay frailty.